Utilizing TikTok as a Digital Marketing Communication Medium Based on Cloud Technology - Rut Tiolina Eloisma Tambunan; Sajudin Ma'ruf; Liza Nadira; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The advancement of information technology has brought about a drastic change in the marketing landscape, with social media becoming one of the primary platforms for reaching a wider audience. One platform that stands out in this regard is TikTok, which offers immense potential as a digital marketing communication medium. The utilization of TikTok as a cloud-based digital marketing communication medium is investigated. Employing a qualitative approach and literature review, an analysis is conducted on how TikTok leverages cloud technology infrastructure to provide efficient and flexible services for marketers. The findings reveal that the integration between TikTok and cloud technology presents new opportunities for marketers to manage and analyze data, optimize campaigns, and enhance consumer engagement more effectively. The practical implications of this discussion are to provide guidance for marketing practitioners in optimally utilizing TikTok as part of their digital marketing strategies.